Teachers’ Factors as Determinant of Pre-Primary School Children Reading Skills in Ekiti State - Ruth Morenike Odewumi (The Eastasouth Journal of Social Science and Humanities, 2026)
The level of preschool children reading skills is declining gradually and this could affect both reading fluency and comprehension of preschool children. There may be a connection between this phenomenon and the country’s falling education. This study therefore examined Teachers’ factors as determinant of reading skills in pre-primary schools in Ijero local government area of Ekiti State. The study was anchored on the recognition of early childhood education as the foundation of lifelong learning, particularly in language and literacy development. A survey research design was adopted, and the population comprised all pre-primary school teachers in the study area. A sample of one hundred (100) teachers drawn from ten pre-primary schools was selected using simple random sampling. Two research instruments Teachers’ Personality Questionnaire (TPQ) and Teachers’ Leadership Questionnaire (TLQ) were used for data collection. The instruments were validated by experts in early childhood education and measurement and evaluation, and their reliability coefficients were established using Cronbach’s alpha. Data collected were analyzed using frequency counts and percentages. Findings revealed that teachers’ personality traits such as patience, enthusiasm, and positive attitude significantly influence pupils’ reading skills. The study also found that teachers’ leadership roles, including motivation, provision of reading materials, and encouragement of independent reading, play a crucial role in enhancing reading fluency and comprehension among pre-primary pupils. The study concludes that effective reading skill acquisition at the pre-primary level depends largely on teachers who possess sound personality attributes and strong leadership qualities. Based on the findings, the study recommended that teachers with sound leadership skills should teach in preschools, Government should encourage the professional teachers especially in preschools through incentives and worthwhile allowance.